Liouville-type Theorems for Semilinear Elliptic Systems (Journal of Partial Differential Equations, 2020)
Liouville-type theorems for a class of semilinear elliptic systems are considered via the method of moving spheres.
Keywords: Liouville-type theorems; Semilinear elliptic systems; Method of moving spheres